Use of nerve elongator to repair short-distance peripheral nerve defects: a prospective randomized study - Lu Bai (Neural Regeneration Research, 2015)
Repair techniques for short-distance peripheral nerve defects, including adjacent joint flexion to reduce the distance between the nerve stump defects, "nerve splint" suturing, and nerve sleeve connection, have some disadvantages. Therefore, we designed a repair technique involving intraoperative tension-free application of a nerve elongator and obtained good outcomes in the repair of short-distance peripheral nerve defects in a previous animal study. The present study compared the clinical outcomes between the use of this nerve elongator and performance of the conventional method in the repair of short-distance transection injuries in human elbows. The 3-, 6-, and 12-month postoperative follow-up results demonstrated that early neurological function recovery was better in the nerve elongation group than in the conventional group, but no significant difference in long-term neurological function recovery was detected between the two groups. In the nerve elongation group, the nerves were sutured without tension, and the duration of postoperative immobilization of the elbow was decreased. Elbow function rehabilitation was significantly better in the nerve elongation group than in the control group. Moreover, there were no security risks. The results of this study confirm that the use of this nerve elongator for repair of short-distance peripheral nerve defects is safe and effective.